Assessing Boreal Peat Fire Severity and Vulnerability of Peatlands to Early Season Wildland Fire - Bourgeau-Chavez, Laura Louise; Grelik, Sarah L.; Billmire, Michael; Jenkins, Liza K.; Kasischke, Eric S.; Turetsky, Merritt R. (Frontiers in Forests and Global Change, 2020)
Globally peatlands store large amounts of carbon belowground with 80% distributed in boreal regions of the northern hemisphere. Climate warming and drying of the boreal region has been documented as affecting fire regimes, with increased fire frequency, severity and extent. While much research is dedicated to assessing changes in boreal uplands, few research efforts are focused on the vulnerability of boreal peatlands to wildfire. In this case study, an integration of field data collection, land cover mapping of peatland types and Landsat-based fire severity mapping was conducted for four spring wildfires where peatlands are abundant in northeastern Alberta Canada. The goal was to better understand if peatlands burn more or less preferentially than uplands in spring fires and how severely the organic soil layers (peat) of different peatland ecotypes burn. Spatial comparisons and statistical analysis showed that proportionally bogs are more likely to burn in spring Alberta wildfires than other ecosystem types, even upland conifer. When fire weather conditions for the duff layers are high, we found that fens become more vulnerable to burning. In addition, bogs experienced greater severity of burn to the peat layers than fens. Due to the small sample size of peat severity in uplands and limited geographic area of this case study, we were unable to assess if bogs are burning more severely than uplands. Further analysis and Landsat algorithm development for organic soil fire severity in peatlands and uplands is needed to more fully understand trends in belowground consumption for wildfires of all seasons and boreal ecotypes.